The High Correlation Between Survey Assessments for Chronic Kidney Disease-Associated Pruritus, and Its Associations with Clinical Outcomes - Huei Hsun Wen; Kinsuk Chauhan; Steven Coca; Juliana Oliveira; Tejas Desai; Keith Huff; Lili Chan (Kidney and Dialysis, 2025)
Background: Chronic kidney disease-associated pruritus (CKD-aP) is a common condition in dialysis patients, and is associated with lower quality of life, depression, and sleep problems. CKD-aP is under-recognized and undertreated. While question 20 of the KDQOL is used for CKD-aP assessment in the clinical setting, recent studies testing novel drugs for CKD-aP have used the WI-NRS. Therefore, evaluating the correlation between KDQOL-Q20 and the WI-NRS may enable the identification of patients who could potentially benefit from these treatments. Methods: This was an observational cohort study of patients receiving in-center hemodialysis from the Mount Sinai Kidney Center. Patients completed a baseline survey on CKD-aP (KDQOL-Q20 and WI-NRS), depression, and sleep quality. A repeat survey was conducted at 4 weeks, with the order of the CKD-aP surveys reversed. We defined moderate/severe CKD-aP as a KDQOL-Q20 score ≥2 and a WI-NRS score ≥ 4. Our outcomes of interest were the correlations of KDQOL-Q20 with the WI-NRS, missed HD treatments, depression, and sleep quality. Correlation analysis was performed with Spearman correlation analysis. Association testing between CKD-aP and outcomes was conducted by relative risk estimation with robust error variance. Results: A total of 112 patients completed the study. According to the WI-NRS, 42% of patients reported itching (score of ≥4) while according to KDQOL-Q20, 57% of patients reported itching (score of ≥2). KDQOL-Q20 and the WI-NRS were strongly correlated (r = 0.7; p < 0.001). Patients who had moderate/severe CKD-aP according to KDQOL-Q20 had a non-statistically significant trend towards a lower risk of missed HD treatments and a higher risk of depression, and a statistically significantly higher risk of sleep-related problems, compared to those with no or mild CKD-aP. Conclusions: CKD-aP is a common condition, and is associated with various clinical outcomes. We found a strong correlation between two CKD-aP measures. These results can help to identify patients for CKD-aP treatment.